Advances in colon capsule endoscopy: a review of current applications and challenges - Gibbons, E.; Kelly, O. B.; Hall, B. (Frontiers in Gastroenterology, 2023)
Colon capsule endoscopy (CCE) has been demonstrated to be comparable to traditional colonoscopy and better than CT colonography (CTC) for the detection of colonic pathology. It has been shown to have a high incremental yield after incomplete colonoscopy. It is a safe test with good patient acceptability. Challenges currently include great variability in completion rates and high rates of re-investigation. In this review, we will discuss the evidence to date regarding CCE in symptomatic and surveillance populations, and in those post incomplete colonoscopy. We will discuss current challenges faced by CCE and areas for further research.